Polyphosphate: A Multifunctional Metabolite in Cyanobacteria and Algae - Sanz-Luque, Emanuel; Bhaya, Devaki; Grossman, Arthur R. (Frontiers in Plant Science, 2020)
Polyphosphate (polyP), a polymer of orthophosphate (PO43-) of varying lengths, has been identified in all kingdoms of life. It can serve as a source of chemical bond energy (phosphoanhydride bond) that may have been used by biological systems prior to the evolution of ATP. Intracellular PolyP is mainly stored as granules in specific vacuoles called acidocalcisomes, and its synthesis and accumulation appear to impact a myriad of cellular functions. It serves as a reservoir for inorganic PO43- and an energy source for fueling cellular metabolism, participates in maintaining adenylate and metal cation homeostasis, functions as a scaffold for sequestering cations, exhibits chaperone function, covalently binds to proteins to modify their activity and enables normal acclimation of cells to stress conditions. PolyP also appears to have a role in symbiotic and parasitic associations, and in higher eukaryotes, low polyP levels seem to impact cancerous proliferation, apoptosis, procoagulant and proinflammatory responses and cause defects in TOR signaling. In this review, we discuss the metabolism, storage, and function of polyP in photosynthetic microbes, which mostly includes research on green algae and cyanobacteria. We focus on factors that impact polyP synthesis, specific enzymes required for its synthesis and degradation, sequestration of polyP in acidocalcisomes, its role in cellular energetics, acclimation processes and metal homeostasis, and then transition to its potential applications for bioremediation and medical purposes.